Czy partie nowe są rzeczywiście nowe? : Polskie partie polityczne w świetle badania opinii ekspertów (Politeja, 2025)
ARE NEW PARTIES REALLY NEW? POLISH POLITICAL PARTIES IN LIGHT OF THE EXPERT SURVEYS RESEARCHThe question of party novelty is of great interest to researchers, but there is also much controversy about what constitutes a new party. Is it only a party that competes based on new ideological and program objectives, or any party that participates in elections for the first time, or perhaps only a party created from scratch or founded by people who have never participated in politics before? What about groupings formed by splits or mergers of other political groups? Parties that are considered new may show continuity with their predecessors in terms of party cadres, electoral programes, policies implemented, or organisational structures. The purpose of this article is to determine which, if any, of the relevant parties participating in the next general election should be considered new, and which are a continuation of one or more pre-existing parties. There exists an expectation that parties representing the post-communist and post-Solidarity roots will show continuity with pre-existing ones, while parties formed outside these options will have the character of genuinely new parties. The above hypotheses are verified based on the empirical research – analysis of the expert survey conducted in 2022. The article points out that the party participating in the election that is not a continuation of a specific predecessor is not necessarily new, as it can be a continuation of several parties that participated in the previous election. For such a party the term ‘amalgamation’ has been coined.